2011
DOI: 10.1098/rsbl.2011.0920
|View full text |Cite
|
Sign up to set email alerts
|

Transgenerational effects of parent and grandparent gender on offspring development in a biparental beetle species

Abstract: Parental effects on offspring life-history traits are common and increasingly well-studied. However, the extent to which these effects persist into offspring in subsequent generations has received less attention. In this experiment, maternal and paternal effects on offspring and grand-offspring were investigated in the biparental burying beetle Nicrophorus vespilloides, using a split-family design. This allowed the separation of prenatal and postnatal transgenerational effects. Grandparent and parent gender we… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

4
23
0

Year Published

2014
2014
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 19 publications
(27 citation statements)
references
References 19 publications
4
23
0
Order By: Relevance
“…We showed that the offspring phenotype results from a combination of multigenerational effects (grand‐parents, parents and offspring), similar to theoretical and other experimental studies (Burggren, ; Hafer et al, ; Kou et al, ; Lock, ; Prizak et al, ; Shama & Wegner, ; Walsh et al, ). However, in our study, grand‐parental and parental effects acted independently (no significant interaction between grand‐parental and parental environmental effects): Either only one affected the offspring environment (behavior), or in interaction with the offspring environment (within‐X transgenerational plasticity) and in opposite directions (shell thickness).…”
Section: Discussionsupporting
confidence: 87%
“…We showed that the offspring phenotype results from a combination of multigenerational effects (grand‐parents, parents and offspring), similar to theoretical and other experimental studies (Burggren, ; Hafer et al, ; Kou et al, ; Lock, ; Prizak et al, ; Shama & Wegner, ; Walsh et al, ). However, in our study, grand‐parental and parental effects acted independently (no significant interaction between grand‐parental and parental environmental effects): Either only one affected the offspring environment (behavior), or in interaction with the offspring environment (within‐X transgenerational plasticity) and in opposite directions (shell thickness).…”
Section: Discussionsupporting
confidence: 87%
“…Experimental work is increasingly documenting how grandmaternal effects alter life-history (Hafer et al 2011;Lock 2012) or phenotypic (Cropley et al 2006) traits over and above maternal effects, but, to our knowledge, experiments assessing the fitness implications after controlling for multigenerational factors have not yet been performed. As expected under Mendelian inheritance (Galton 1897), Eð WÞ appears more sensitive to changes in m than g during both the transient and new equilibrium phases.…”
Section: Discussionmentioning
confidence: 99%
“…Transgenerational effects are not restricted to the maternal generation, however. Phenotypic "memory", often provoked by environmental factors, can persist for many successive generations (Molinier et al 2006) and may differ depending on the sex of the influencing ancestor (Lock 2012). In particular, levels of grandmaternal nutrition can, over and above maternal effects, alter lifehistory traits in the collembolan Folsomia candida (Hafer et al 2011), obesity in humans (Cropley et al 2006), and mass in white-tailed deer Odocoileus virginianus (Mech et al 1991).…”
Section: Introductionmentioning
confidence: 99%
See 1 more Smart Citation
“…grand-parental effect) (e.g. Hafer et al 2011;Herman and Sultan 2011;Kou et al 2011;Lock 2012;Walsh et al 2014). However, it is unclear how multigenerational effects can interact (Prizak et al 2014) and experimental works controlling for combination of multigenerational effects always showed complex patterns of phenotypic offspring responses.…”
Section: Introductionmentioning
confidence: 99%